Development and Validation of GC-ECD Method for the Determination of Metamitron in Soil - Shishir Tandon; Satyendra Kumar; N. K. Sand (International Journal of Analytical Chemistry)
This paper aims at developing and validating a convenient, rapid, and sensitive method for estimation of metamitron from soil samples.Determination andquantification was carried out by Gas Chromatography on microcapillary column with an Electron Capture Detector source. The compound was extracted from soil using methanol and cleanup by C-18 SPE. After optimization, the method was validated by evaluating the analytical curves, linearity, limits of detection, and quantification, precision (repeatability and intermediate precision), and accuracy (recovery). Recovery values ranged from 89 to 93.5% within 0.05- 2.0 µg L−1 with average RSD 1.80%. The precision (repeatability) ranged from 1.7034 to 1.9144% and intermediate precision from 1.5685 to 2.1323%. Retention time was 6.3 minutes, and minimum detectable and quantifiable limits were 0.02 ng mL−1 and 0.05 ng g−1, respectively. Good linearity (R2=0.998) of the calibration curves was obtained over the range from 0.05 to 2.0 µg L−1. Results indicated that the developed method is rapid and easy to perform, making it applicable for analysis in large pesticide monitoring programmes.